2016
DOI: 10.1186/s12933-016-0434-1
|View full text |Cite
|
Sign up to set email alerts
|

Adequate vitamin D status is associated with the reduced odds of prevalent diabetic retinopathy in African Americans and Caucasians

Abstract: BackgroundVitamin D status has been hypothesized to protect against development of diabetic retinopathy via its anti-inflammatory and anti-angiogenic properties. Additionally, in vitro and in vivo studies suggest vitamin D favorably influences blood pressure and blood glucose control, strong risk factors for diabetic retinopathy. We examined the association between vitamin D status and prevalent diabetic retinopathy in participants with diabetes from a population-based cohort.MethodsAmong participants in the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…Some studies have opposite results. Millen et al [9] found that, after follow-up for 3 years, compared to patients with serum 25OHD < 30 nmol/l, patients with serum 25OHD ≥ 75 nmol/l had significant lower risk of DR after adjustment for covariates [OR 0.47 (95 % CI 0.23-0.96)], while no statistically significant association was observed between vitamin D and PDR. A prospective study of 936 type 2 diabetic patients also failed to yield a significant association between vitamin D status and the onset or progression of PDR after follow-up for 5 years [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have opposite results. Millen et al [9] found that, after follow-up for 3 years, compared to patients with serum 25OHD < 30 nmol/l, patients with serum 25OHD ≥ 75 nmol/l had significant lower risk of DR after adjustment for covariates [OR 0.47 (95 % CI 0.23-0.96)], while no statistically significant association was observed between vitamin D and PDR. A prospective study of 936 type 2 diabetic patients also failed to yield a significant association between vitamin D status and the onset or progression of PDR after follow-up for 5 years [10].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is considered as a dichotomous variable (VDD vs. non-VDD). Data regarding effect of vitamin D deficiency on DR were available from twelve trials plus our study conducted [6,9,[17][18][19][20][21][22][23][24][25][26]. Risk of DR in VDD individuals might rise by 35 %, compared with non-VDD (OR = 1.35, 95 % CI 1.11-1.64) (▶ Fig.…”
Section: Vitamin D and Drmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the classical role in skeleton and bone health, vitamin D (VD) has been identified to exert non-classical pleiotropic e f f e c t s s u c h a s a n t i -i n fl a m m a t o r y, a n t i a n g i o g e n i c , a n t i p r o l i f e r a t i v e , a n d immunomodulatory properties (5). It is also considered to positively regulate hypertension and blood glucose levels (6). Moreover, it has been established that maintaining VD at adequate levels can be a useful technique to prevent type 2 diabetes mellitus (T2DM) (7).…”
Section: There Are Various Risk Factors That Have Been Suspected In Tmentioning
confidence: 99%
“…Accumulating evidence from some epidemiologic studies suggest that vitamin D status may be a novel modifiable risk factor for DR [6,7,[24][25][26]. There is some experimental evidence on the preventive effect of vitamin D in the development of DR in a rodent model, In vitro and in vivo studies suggested that vitamin D affects blood pressure and blood glucose control, which are the strong risk factors for DR [5].…”
Section: Introductionmentioning
confidence: 99%